2018
DOI: 10.1002/smj.2741
|View full text |Cite
|
Sign up to set email alerts
|

Strategy processes and practices: Dialogues and intersections

Abstract: Research Summary: Building on our review of the strategy process and practice research, we identify three ways to see the relationships between the two research traditions: complementary, critical, and combinatory views. We adopt in this special issue the combinatory view, in which activities and processes are seen as closely intertwined aspects of the same phenomena. It is this view that we argue offers both strategy practice and strategy process scholars some of the greatest opportunities for joint research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
170
0
19

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(210 citation statements)
references
References 222 publications
(309 reference statements)
4
170
0
19
Order By: Relevance
“…The dwindling number of strategic planning studies has been noted by several authors (Bryson, Edwards, & Van Slyke, ; Whittingon & Cailluet, ; Wolf & Floyd, ). Although highly reputable peer‐reviewed journals have recently given space for the publication of strategy management and strategy processes (see Burgelman et al, ; Gans & Ryal, ; Kin, Howard, Pahnke, & Boeker, ; O'Regan, Kling, Ghobadian, & Perren, ; Thomas & Ambrosini, ), these papers tend to look more at the strategy formation and strategy development, often on the use of strategy tools and techniques (see Arend, Zhao, Song, & Im, ; Jarzabkowski, Giulietti, Oliveira, & Amoo, ; Tassabehji & Isherwood, ; Vuorinen, Hakala, Kohtamäki, & Uusitalo, ) and with few putting the strategy into action (strategy implementation). Hambrick and Cannella Jr. (), p. 278) stated that “ without successful implementation, a strategy (plan) is but a fantasy.…”
Section: Introductionmentioning
confidence: 99%
“…The dwindling number of strategic planning studies has been noted by several authors (Bryson, Edwards, & Van Slyke, ; Whittingon & Cailluet, ; Wolf & Floyd, ). Although highly reputable peer‐reviewed journals have recently given space for the publication of strategy management and strategy processes (see Burgelman et al, ; Gans & Ryal, ; Kin, Howard, Pahnke, & Boeker, ; O'Regan, Kling, Ghobadian, & Perren, ; Thomas & Ambrosini, ), these papers tend to look more at the strategy formation and strategy development, often on the use of strategy tools and techniques (see Arend, Zhao, Song, & Im, ; Jarzabkowski, Giulietti, Oliveira, & Amoo, ; Tassabehji & Isherwood, ; Vuorinen, Hakala, Kohtamäki, & Uusitalo, ) and with few putting the strategy into action (strategy implementation). Hambrick and Cannella Jr. (), p. 278) stated that “ without successful implementation, a strategy (plan) is but a fantasy.…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of a firm's strategy through daily leadership activities is one of the CEO's primary tasks (Burgelman et al, 2018;Simsek et al, 2015). Successful implementation of a firm's strategy through daily leadership activities is one of the CEO's primary tasks (Burgelman et al, 2018;Simsek et al, 2015).…”
Section: The Ceo's Role In the Implementation Of An Randd-intensive Invmentioning
confidence: 99%
“…U nderstanding how CEOs influence firm strategies and outcomes have received growing research interest recently (Burgelman et al, 2018;Liu et al, 2018). A rise in the importance of CEOs' general managerial skills has been observed as one of the most striking trends in the past half century (Crossland et al, 2014), and stemming from this observation, recent research has shown that S&P 1500 firms with 'generalist' CEOs exhibit higher innovation outcomes (Custódio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strategy processes and practices are needed more than ever to help managers make sense of their challenges and anticipate or respond to ongoing developments in today's rapidly changing environments in a strategic manner (Burgelman et al, 2018;Hutzschenreuter & Kleindienst, 2006;Wolf & Floyd, 2013). As an important voice in the field, Hamel (2009, p. 3) claims that we should "reinvent strategy making as an emergent process".…”
Section: Introductionmentioning
confidence: 99%
“…As will be shown, this is a strong case for addressing this phenomenon. Now, to better understand strategy emergence in this organizational context, we build a theoretical framework that is grounded in processual conceptions of organizational change (Beech & MacIntosh, 2012;Langley, Smallman, Tsoukas, & Van de Ven, 2013;Tsoukas & Chia, 2002) and current practice-theoretical descriptions of emergent strategies (Burgelman et al, 2018;Chia & Holt, 2009;Mirabeau & Maguire, 2014;Vaara & Whittington, 2012). Research on strategy-as-practice suggests that strategy is something that people in organizations do, as compared to something that an organization has (Johnson, Langley, Melin, & Whittington, 2007;Whittington, 2006).…”
Section: Introductionmentioning
confidence: 99%